2020
DOI: 10.1186/s13213-020-01547-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community profiles grown on 1020 carbon steel surfaces in seawater-isolated microcosm

Abstract: Corrosion of metallic alloys is a concern worldwide, with impacts affecting different production sectors and consequent economic losses in the order of billions of dollars annually. Biocorrosion is a form of corrosion where the participation of microorganisms can induce, accelerate, or inhibit corrosive processes. In this study, it was evaluated that the changes in profile communities, by the sequencing of the 16S ribosomal gene, grown over steel coupons in a microcosm with no additional oxygen supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Besides, previous study also showed that Ponticaulis sp. was one of the main colonizers for the metallic alloys ( Procópio, 2020 ). It suggested that the Oleibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous study also showed that Ponticaulis sp. was one of the main colonizers for the metallic alloys ( Procópio, 2020 ). It suggested that the Oleibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the class Bacilli in the Firmicutes phylum were particularly enriched on the metal surfaces, thus possibly explaining the observed corrosion on these surfaces. Previous works have found that certain species of the genus Bacillus , such as the B. cereus found on some of the metal pier surfaces, can accelerate the pitting corrosion of steel surfaces in soils [ 52 , 53 ] and aquatic environments [ 24 ]. Although the corrosion-related bacteria remained at low relative abundances on the pier surfaces, they nevertheless can serve as an indicator that maintenance work is required to preserve the esthetic appearance of the metal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some microbial residents of surfaces are considered stress-tolerant and they may in turn participate in biochemical processes that influence various properties of the surfaces [ 23 ]. For example, on inert surfaces such as stone and steel, some microbes can induce or accelerate corrosion [ 24 ], while other microbes can prevent biodeterioration [ 25 ]. The taxonomic composition of microbes residing on corroded steel surfaces has been found to vary by surface type, surface material, and environmental conditions (e.g., salinity), but the composition of their metabolic functions is relatively conserved [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the class Bacilli in the Firmicutes phylum were particularly enriched on the metal surfaces, thus possibly explaining the observed corrosion on these surfaces. Previous works have found that certain species of the genus Bacillus, such as the B. cereus found on some of the metal pier surfaces, can accelerate the pitting corrosion of steel surfaces in soils [49,50] and aquatic environments [21]. Although the corrosion-related bacteria remained at low relative abundances on the pier surfaces, they nevertheless can serve as an indicator that maintenance work is required to preserve the esthetic appearance of the metal surfaces.…”
Section: Preferential Enrichment Of Taxa Across Surface Types and Materialsmentioning
confidence: 99%
“…Therefore, some microbial residents of surfaces are considered stress-tolerant and they may in turn participate in biochemical processes that influence various properties of the surfaces [20]. For example, on inert surfaces such as stone and steel, some microbes can induce or accelerate corrosion [21], while other microbes can prevent biodeterioration [22]. The taxonomic composition of microbes residing on corroded steel surfaces has been found to vary by surface type, surface material, and environmental conditions (e.g., salinity), but the composition of their metabolic functions is relatively conserved [23].…”
Section: Introductionmentioning
confidence: 99%